Junk - Burgess, Melvin (London Penguin Books, 1996)
Tells, in the voices of many individuals, of two fourteen-year-old runaways in Bristol, England, who find a home with anarchists and get involved in vandalism, shoplifting, and prostitution to support their growing addiction to heroin
Carnegie Medal, 1996
Guardian Award for Children's Fiction, 1997
1
Keywords: Anarchists -- Fiction; Drug abuse -- Fiction; Heroin -- Fiction; Prostitution -- Fiction; Runaways -- Fiction; England -- Fiction